Judicial Activism gives recognition to a general class action in South Africa - De Vos, Wouter (Juta & Company Ltd. * Juta Law, 2013)
After decades of debates on the viability of class actions in South Africa the supreme court of appeal has finally given recognition to a general class action for damages. There is clear authority, preceding the judgment under discussion, that section 38(c) of the Constitution of the Republic of South Africa, 1996, provides a sufficient basis for the institution of a class action to enforce any constitutional right. The lack of legislation regulating these complicated proceedings has, therefore, not been viewed as an impediment to the prosecution of a large number of such similar claims in this manner. This has happened in the respective judgments of Froneman J, in Ngxuza v Permanent Secretary, Department of Welfare, Eastern Cape (2001 2 SA 609 (E)) and Cameron JA, in Permanent Secretary, Department of Welfare, Eastern Cape v Ngxuza (2001 4 SA 1184 (SCA)).